The genome sequence of the painted lady, Vanessa cardui Linnaeus 1758 [version 1; peer review: 2 approved] - Gerard Talavera; Charlotte Wright; Aurora García-Berro; Konrad Lohse (Wellcome Open Research, 2021)
We present a genome assembly from an individual female Vanessa cardui (the painted lady; Arthropoda; Insecta; Lepidoptera; Nymphalidae). The genome sequence is 425 megabases in span. The majority of the assembly is scaffolded into 32 chromosomal pseudomolecules, with the W and Z sex chromosome assembled. Gene annotation of this assembly on Ensembl has identified 12,821 protein coding genes.